Assenze, presenze e prospettive del paesaggio naturale nello Zibaldone - Medda, Veronica (Rivista Internazionale di Studi Leopardiani, 2025)
This essay discusses the key theme of nature in Leopardi, with a focus on the term ‘landscape’ in the Zibaldone. During that period, this concept evolved from a purely humanistic dimension to a more scientific one, allowing for a deeper exploration of the relationship between humans and nature. The aim is to suggest the possibility of an ethical-environmental use of modern literature.